SEISMIK VULNERABILITY INDEX ANALYSIS IN NAGARI MALALAK TIMUR AS AN EFFORT TO DETERMINE LANDSLIDE POTENTIAL AREAS THE HVSR METHOD - Silitonga, Yese Angga Marito; Syafriani, Syafriani (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2024)
Nagari Malalak Timur, Malalak Subdistrict, Agam Regency has experienced landslides caused by soil movement so that the soil conditions become unstable. Landslides are also influenced by external factors such as vibrations from earthquakes and vibrations from human activities. For this reason, a study was conducted to describe the distribution of seismic vulnerability index as an effort to determine the potential landslide area. The sampling was limited to 10 measurement points using a set of seismograph sysmatrack MAE sensor type S3S. The basic principle of HVSR method is to obtain the value of Dominant Frequency (f0) and Amplification Factor (A0) by comparing the value of horizontal component and vertical component of microtremor data. From the value of Dominant Frequency (f0) and Amplification Factor (A0), the calculation of Dominant Period (T0) and Seismic Susceptibility Index (Kg) can be done. The results of research in Nagari Malalak Timur show the value of Dominant Frequency (f0) is in the range of 2.676 - 7.22 Hz. The Amplification Factor (A0) value is in the range of 1.4 - 6.563. The Dominant Period (T0) value is in the range of 0.138 - 0.373 s. The Seismic Susceptibility Index (Kg) value is in the range of 0.365 - 14.62 cm/s2. Based on the distribution of Seismic Susceptibility Index (Kg) values in the 10 research points, the highest landslide potential is in point D with a Seismic Susceptibility Index (Kg) value of 14.62 cm/s2. This causes landslides to occur at any time.Keywords: Amplification Factor, Dominant Frequency, HVSR, Seismic Susceptibility Index